Modification of the existing maximum residue level for deltamethrin in cherries - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer SAS submitted a request to the competent national authority in France to modify the existing maximum residue level (MRL) for the active substance deltamethrin in cherries. The data submitted in support of the request were found to be sufficient to derive a MRL proposal for cherries. Adequate analytical methods for enforcement are available to control the residues of deltamethrin on the commodity under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of deltamethrin according to the reported agricultural practices is unlikely to present a risk to consumer health. The risk assessment shall be regarded as indicative and affected by non‐standard uncertainties, due to the lack of information on the actual occurrence of residues of trans‐deltamethrin and alpha‐R‐deltamethrin in certain crops and on the toxicological profile of both isomers. Furthermore, also information on the metabolism of these isomers in livestock and adequate livestock feeding studies in cows and hens, investigating residues in all relevant tissues and matrices according to the residue definitions for monitoring and risk assessment simultaneously, are still missing.